(untitled) (Nepalese Journal of Radiology, 2021)
Introduction: Chance fracture is a horizontal fracture of the vertebra extending from the posterior element to the vertebral body due to flexion-distraction injury and is potentially unstable. The aim of this study was to evaluate the demography and Computed Tomography scan findings in Chance fracture of the spine. Method: A retrospective study was conducted at the National Trauma Center, National Academy of Medical Sciences over a period of one year (December 2019 to December 2020). Demographic data, mechanism of injury, and computed tomographic findings of Chance fracture were recorded. Result: Computed tomography scans of 41 patients with Chance fracture were identified. Fall injury (76%) was the most common cause of Chance fracture followed by road traffic accidents. This fracture was most commonly seen in thoracolumbar junction TLJ (D10-L2); with L1 being the most affected vertebra (36.5%). Among posterior elements, facet distraction (84%) was the most common finding followed by lamina fracture (83%), and pedicle fracture (68%). Regarding vertebral body fracture, involvement of both superior and inferior endplates were common than isolated involvement of either one of them. CT revealed that a burst component was a common finding (68%) in Chance fracture. Conclusion: Chance fracture was commonly caused by fall injury in our context which is higher in incidence than previously reported. More than half of patients with Chance fracture also had Burst-type components that could influence surgical management. Computed tomography scans is a useful imaging modality for the assessment of Chance fracture and burst component.